Behavior and Factors Influencing Students Riding Motorcycles Without a License to School - Amalia, Hasna Shofy; Brilianti, Dani Fitria (Kirana Publisher (KNPub), 2024)
In Indonesia, underage motorcycle riders are frequently found operating vehicles without a valid driver's license, raising significant safety and legal concerns. This study aims to explore the motivations and behaviors of these underage riders, as well as the factors contributing to their non-compliance with traffic regulations. Conducted at SMAN 1 Randudongkal with 114 respondents, the research employed a quantitative descriptive approach. This method systematically analyzes numerical data to provide an in-depth understanding of a population or phenomenon, focusing on descriptive insights rather than causal relationships. Data collection was carried out through a structured questionnaire distributed via Google Forms. The analysis revealed that the primary motivations for students riding motorcycles to school without licenses are